(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The history of copyright protection has followedtwo separate streams, one relating to the rights of authors of literary andartistic works and the other relating to the contributions of others who addvalue in the presentation of literary and artistic works to the public: theseinclude performing artists such as actors, dancers, singers and musicians,producers of phonograms including CDs and broadcasting organizations. Thesecontributions are generally referred to as ’related’ or ’neighbouring’ rightsbecause they are related to or neighbouring upon the main authors’ rights. Thetwo treaties that deal with the authors’ rights are the Berne Convention andthe Universal Copyright Convention (UCC).